Anglophone Picturebook Shared Reading in Chinese Families: A Typology Exploring Parent-Child Interaction Patterns - Zou, Ying (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2023)
This study examined parent-child interactions during foreign-language shared reading of Anglophone picturebooks at home by Chinese parents. It is among the first to probe foreign-language shared reading in the home setting. Data was obtained from in-depth ethnographic observation of seven parent-child dyads and from interviews, with a survey comprising 565 parent respondents providing background for this wider evidence. A grounded theory approach was applied to generate a new, five-part typology of Chinese parents' English picturebook reading practices. This new typology reveals the diversity of parent-child interaction processes by categorizing them according to five foci: the literal focus, the literacy skill focus, the literary focus, the exploratory focus and the digital focus. The findings of this study may have a reciprocal effect on the study of first- and second-language shared reading practices and can be applied to analysis of or intervention in shared reading, at home or in school settings.